Ataxin-3 Links NOD2 and TLR2 Mediated Innate Immune Sensing and Metabolism in Myeloid Cells - Chapman, Thomas P.; Corridoni, Daniele; Shiraishi, Seiji; Pandey, Sumeet; Aulicino, Anna; Wigfield, Simon; do Carmo Costa, Maria; Thézénas, Marie-Laëtitia; Paulson, Henry; Fischer, Roman; Kessler, Benedikt M.; Simmons, Alison (Frontiers in Immunology, 2019)
The interplay between NOD2 and TLR2 following recognition of components of the bacterial cell wall peptidoglycan is well-established, however their role in redirecting metabolic pathways in myeloid cells to degrade pathogens and mount antigen presentation remains unclear. We show NOD2 and TLR2 mediate phosphorylation of the deubiquitinase ataxin-3 via RIPK2 and TBK1. In myeloid cells ataxin-3 associates with the mitochondrial cristae protein MIC60, and is required for oxidative phosphorylation. Depletion of ataxin-3 leads to impaired induction of mitochondrial reactive oxygen species (mROS) and defective bacterial killing. A mass spectrometry analysis of NOD2/TLR2 triggered ataxin-3 deubiquitination targets revealed immunometabolic regulators, including HIF-1α and LAMTOR1 that may contribute to these effects. Thus, we define how ataxin-3 plays an essential role in NOD2 and TLR2 sensing and effector functions in myeloid cells.